Britain's Health Services (London : Communist Party of Great Britain)
1942-10 1942 1940s 40 pages ISSUED BY THE COMMUNIST PARTY OF GREAT BRITAIN 16 KING STREET, LONDON, W.C.2 October 1942 PRINTED BY LANGLEY AND SONS. LTD. THE EUSTON PRESS. N.W.1. 15X/2/103/252